Tricistronic expression of MOAP-1, Bax and RASSF1A in cancer cells enhances chemo-sensitization that requires BH3L domain of MOAP-1 - Lee, Y. H.; Pang, Siew Wai *; Revai Lechtich, E.; Shah, K.; Simon, S. E.; Ponnusamy, S.; Narayanan, R.; Poh, Chit Laa *; Tan, Kuan Onn * (Springer, 2020)
Purpose: Although important for apoptosis, the signaling pathway involving MOAP-1(Modulator of Apoptosis 1), RASSF1A (RAS association domain family 1A), and Bax (Bcl-2 associated X protein) is likely to be dysfunctional in many types of human cancers due to mechanisms associated with gene mutation and DNA hyper-methylation. The purpose of the present study was to assess the potential impact of generating physiologically relevant signaling pathway mediated by MOAP-1, Bax, and RASSF1A (MBR) in cancer cells and chemo-drug resistant cancer cells. Methods: The tricistronic expression construct that encodes MOAP-1, Bax, and RASSF1A (MBR) or its mutant, MOAP-1∆BH3L, Bax and RASSF1A (MBRX) was expressed from an IRES (Internal Ribosome Entry Site)-based tricistronic expression vector in human breast cancer cells, including MCF-7, MCF-7-CR (cisplatin resistant) and triple negative breast cancer cells, BMET05, for functional characterization through in vitro and in vivo models. Results: Transient expression of MBR potently promoted dose-dependent apoptotic signaling and chemo-sensitization in the cancer cells, as evidenced by loss of cell viability, nuclei condensation and Annexin-V positive staining while stable expression of MBR in MCF-7 cells significantly reduced the number of MBR stable clone by 86% and the stable clone exhibited robust chemo-drug sensitivity. In contrast, MBRX stable clone exhibited chemo-drug resistance while transiently over-expressed MOAP-1ΔBH3L inhibited the apoptotic activity of MBR. Moreover, the spheroids derived from the MBR stable clone displayed enhanced chemo-sensitivity and apoptotic activity. In mouse xenograft model, the tumors derived from MBR stable clone showed relatively high level of tumor growth retardation associated with the increase in apoptotic activity, leading to the decreases in both tumor weight and volume. Conclusions: Expression of MBR in cancer cells induces apoptotic cell death with enhanced chemo-sensitization requiring the BH3L domain of MOAP-1. In animal model, the expression of MBR significantly reduces the growth of tumors, suggesting that MBR is a potent apoptotic sensitizer with potential therapeutic benefits for cancer treatment.